TiO ISOTOPES BANDS IN THE M DWARF SPECTRA - Ivanyuk, O.; Pavlenko, Ya. V.; Jones, H.R.A.; Penfield, D.; Clarke, J.R.A. (Одеські астрономічні публікації, 2010)
A few TiO isotopes are responsible for formation different molecular features in M-Dwarfs. We present spectral analysis for moleculrar spectrum TiO (Schwenke 1998) consists of 5 Titanium isotopes: 46Ti, 47Ti, 48Ti, 49Ti, 50Ti. Results denote most influent isotopes in our observational spectrum. Our main aim is to find some remarkable isotope features in the observed spectra of M Dwarf.